Mapping sub-cellular protein aggregates and lipid inclusions using synchrotron ATR-FTIR microspectroscopy - Hartnell, David; Hollings, Ashley; Ranieri, Anna Maria; Lamichhane, Hum Bahadur; Becker, Thomas; Sylvain, Nicole J.; Hou, Huishu; Pushie, M.J.; Watkin, Elizabeth; Bambery, K.R.; Tobin, M.J.; Kelly, Michael E.; et al. (ROYAL SOC CHEMISTRY, 2021)
Visualising direct biochemical markers of cell physiology and disease pathology at the sub-cellular level is an ongoing challenge in the biological sciences. A suite of microscopies exists to either visualise sub-cellular architecture or to indirectly view biochemical markers (e.g. histochemistry), but further technique developments and innovations are required to increase the range of biochemical parameters that can be imaged directly, in situ, within cells and tissue. Here, we report our continued advancements in the application of synchrotron radiation attenuated total reflectance Fourier transform infrared (SR-ATR-FTIR) microspectroscopy to study sub-cellular biochemistry. Our recent applications demonstrate the much needed capability to map or image directly sub-cellular protein aggregates within degenerating neurons as well as lipid inclusions within bacterial cells. We also characterise the effect of spectral acquisition parameters on speed of data collection and the associated trade-offs between a realistic experimental time frame and spectral/image quality. Specifically, the study highlights that the choice of 8 cm-1 spectral resolutions provide a suitable trade-off between spectral quality and collection time, enabling identification of important spectroscopic markers, while increasing image acquisition by ∼30% (relative to 4 cm-1 spectral resolution). Further, this study explores coupling a focal plane array detector with SR-ATR-FTIR, revealing a modest time improvement in image acquisition time (factor of 2.8). Such information continues to lay the foundation for these spectroscopic methods to be readily available for, and adopted by, the biological science community to facilitate new interdisciplinary endeavours to unravel complex biochemical questions and expand emerging areas of study.